2020
DOI: 10.1177/1178630220972957
|View full text |Cite
|
Sign up to set email alerts
|

Change in Compliance of Staff at 4 Vietnam Universities after the Enactment of Smoke-free Environment Decree

Abstract: Background: The Tobacco Control Law in Vietnam was adopted in 2012 and came into force from May 2013, followed by a number of guiding sub-law legal documents. Smoke-free campus policy in university is considered an important measure to protect people from secondhand smoking as well as staffs and students will be in favour of the policy. Furthermore, there has been evidence suggested that smoke-free policy had positive impact on active smoking as well as anti-smoking attitude. Methods: A cross-sectional self-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…the students and staff of a university in Malaysia, but without a smoke-free policy, showed a prevalence of smoking of 18.3% (Nurul 'Izzati et al, 2016). Several studies from other countries involving similar populations of university communities implementing the smoke-free campus policy also reported a lower prevalence of smoking as compared to the general population such as in the United Kingdom (Bartington et al, 2020), the United States (Blake et al, 2020;Wray et al, 2020), Western Australia (Burns et al, 2013) and Vietnam (Nguyen et al, 2020).…”
Section: A Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…the students and staff of a university in Malaysia, but without a smoke-free policy, showed a prevalence of smoking of 18.3% (Nurul 'Izzati et al, 2016). Several studies from other countries involving similar populations of university communities implementing the smoke-free campus policy also reported a lower prevalence of smoking as compared to the general population such as in the United Kingdom (Bartington et al, 2020), the United States (Blake et al, 2020;Wray et al, 2020), Western Australia (Burns et al, 2013) and Vietnam (Nguyen et al, 2020).…”
Section: A Discussionmentioning
confidence: 93%
“…Increased knowledge had been associated with implementation of the smoke-free policy in many different populations in Malaysia and in other countries (Smith & Umenai, 2000;Haddad & Malak, 2002;Lim et al, 2017;Jaafar et al, 2019;Quintana et al, 2019;Alves, Precioso & Becoña, 2020). A 2-phase cross-sectional study of undergraduate students in Vietnam showed significant increases in knowledge of the harmful effect of smoking and of smoke-free legislation 1 year after the enactment of Vietnamese Tobacco Control Legislation (Nguyen et al, 2020).…”
Section: A Discussionmentioning
confidence: 99%